2015
DOI: 10.22610/jebs.v7i4(j).591
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consumer Animosity and Consumer Ethnocentrism on Intention to Purchase Foreign Products: The Case of Chinese Branded Household Appliances in Vietnam Market

Abstract: Vietnam-China bilateral relationship has sharply declined due to the recent conflicts on both economic and political affairs. On top of that, the current controversial incident regarding the East Sea issue has constantly deteriorated the connection. At this critical time when the effects of consumers’ attitude toward Chinese products could not be overlooked, the empirical study aims to investigate the impacts of Consumer Animosity and Consumer Ethnocentrism on Purchase Intention of Chinese branded merchandis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…Giang (2015) illustrated that consumer animosity could negatively impact product judgment in their research on Vietnamese consumers' intention to purchase Chinese household appliances, which illustrated how consumer animosity significantly influences product judgment. There are other studies in which consumer animosity is not deemed to be a significant factor.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Giang (2015) illustrated that consumer animosity could negatively impact product judgment in their research on Vietnamese consumers' intention to purchase Chinese household appliances, which illustrated how consumer animosity significantly influences product judgment. There are other studies in which consumer animosity is not deemed to be a significant factor.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In a study on consumers in Italy, the country image was found to be an important aspect that is affected by animosity, which leads to the damage of the receptivity for products (De Nisco et al ., 2013). In an investigation into Vietnamese consumers' perception of Chinese products, Giang (2015) illustrated the effect of animosity on purchase intention, ethnocentrism, and product judgment. Albayati et al .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies related to the purchase of domestic and foreign products have found that when attitude towards and intention to purchase are positive, the consumer is highly likely to purchase that product (Giang & Khoi, 2015). Empirical evidence in this area found that ethnocentric consumers demonstrate a negative attitude that, in turn, affects their intention to purchase foreign products (Sharma et al, 1995;Giang & Khoi, 2015;Kumar et al, 2009;He & Wang, 2015;Josiassen et al, 2011). Thus, based on the previous findings in the literature, consumer ethnocentrism is negatively related to purchase intention toward foreign products.…”
Section: Consumer Ethnocentrism and Intentionmentioning
confidence: 78%
“…Based on the concept of consumer ethnocentrism, ethnocentric consumers have a strongly favourable attitude toward local products rather than foreign products. Previous studies found that consumer ethnocentrism negatively affects attitudes toward foreign products (Batra et al, 2000;Giang & Khoi, 2015;Hamin & Elliott, 2006;He & Wang, 2015;Nijssen et al, 1999;Shankarmahesh, 2006;Sharma et al, 1995;Shimp & Sharma, 1987;Tsai et al, 2013;Watson & Wright, 2000). This indicates that consumers have positive feelings toward domestic products and a bias against foreign products.…”
Section: Hypothesis Development Consumer Ethnocentrism and Attitudementioning
confidence: 92%
See 1 more Smart Citation